2005
DOI: 10.7202/021843ar
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of CO2 – Induced Warming on Downhill Skiing in the Laurentians

Abstract: À l'aide des deux scénarios de variation climatique retenus par le Centre d'étude canadien sur le climat, les auteurs tentent de cerner quel serait l'effet, sur la pratique du ski alpin dans les basses Laurentides, des changements de température et de précipitation prévisibles selon ces scénarios. Ces derniers prévoient une augmentation de la moyenne hivernale des précipitations et des températures s'échelonnant respectivement entre 0 et 16% et 7,6 et 9,3° F (4,2 et 5,2° C). De tels changements pourraient abré… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 2 publications
0
9
0
1
Order By: Relevance
“…When snowmaking was accounted for, Scott et al (2003Scott et al ( , 2006 found that the vulnerability of ski areas in the Canadian provinces of Ontario and Quebec was reduced substantially compared to that reported in earlier studies that did not include snowmaking (McBoyle & Wall 1987, 1992, Lamothe & Périard Consultants 1988.…”
Section: Introductionmentioning
confidence: 85%
“…When snowmaking was accounted for, Scott et al (2003Scott et al ( , 2006 found that the vulnerability of ski areas in the Canadian provinces of Ontario and Quebec was reduced substantially compared to that reported in earlier studies that did not include snowmaking (McBoyle & Wall 1987, 1992, Lamothe & Périard Consultants 1988.…”
Section: Introductionmentioning
confidence: 85%
“…This assumption has been shaken by questions of system complexity (McCool, 2015), global environmental risks (Young, Higham, & Reis, 2014) and natural disasters (Faulkner, 2001). The relationships linking tourism development and the global climate crisis, for example, were first brought to the attention of the academic community by Wall in the 1980s (McBoyle &Wall, 1987;Wall, 1993;Wall, Harrison, Kinnaird, McBoyle, & Quinlan, 1986).…”
Section: Tourism and The Sustainability Traditionmentioning
confidence: 99%
“…The most detailed studies cover areas such as the European Alps (Breiling & Charamza, 1999;Elsasser & Buerki, 2002;Elsasser & Messerli, 2001;Fazzinni, Fratianni, Biancoti, Biscu, & Zasso, 2003;König & Abegg, 1997), North America (Brotton & Wall, 1993;Hamilton, Rohall, Brown, Hayward, & Keim, 2003;Harrison, Kinnaird, McBoyle, Quinlan, & Wall, 1986;Lipski & McBoyle, 1991;Lynch, McBoyle, & Wall, 1981;, 1987Ordower, 1995;Scott, McBoyle, & Mills, 2003;Scott, McBoyle, Mills, & Minogue, 2004) and the Antipodes (Barringer, 1989;Galloway, 1988;König, 1998). The effects of climate change in a Scottish winter sports context also feature in the literature, (Perry, 1971(Perry, , 1972, but much of this work is set within broader discussions about climate change effects yearround in Scotland (Harrison, Winterbottom, & Sheppard, 1999).…”
Section: Climate Change Winter Sports and Tourismmentioning
confidence: 97%